Pemphigus vulgaris is characterized by low IgG reactivities to specific self‐antigens along with high IgG reactivity to desmoglein 3. Issue 3 (November 2014) - Fattal, Ittai; Rimer, Jacob; Shental, Noam; Molad, Yair; Gabrielli, Armando; Livneh, Avi; Sarig, Ofer; Goldberg, Ilan; Gafter, Uzi; Domany, Eytan; Cohen, Irun R.
Summary Pemphigus vulgaris (PV) is an autoimmune skin disease, which has been characterized by IgG autoantibodies to desmoglein 3. Here we studied the antibody signatures of PV patients compared with healthy subjects and with patients with two other autoimmune diseases with skin manifestations (systemic lupus erythematosus and scleroderma), using an antigen microarray and informatics analysis. We now report a previously unobserved phenomenon – patients with PV, compared with the healthy subjects and the two other diseases, show a significant decrease in IgG autoantibodies to a specific set of self‐antigens. This novel finding demonstrates that an autoimmune disease may be associated with a loss of specific, healthy IgG autoantibodies and not only with a gain of specific, pathogenic IgG autoantibodies.